Multicenter, Observational Cohort Study Evaluating Third-Generation Cephalosporin Therapy for Bloodstream Infections Secondary to Enterobacter, Serratia, and Citrobacter Species - Caroline Derrick; P. Brandon Bookstaver; Zhiqiang K. Lu; Christopher M. Bland; S. Travis King; Kayla R. Stover; Kathey Rumley; Shawn H. MacVane; Jenna Swindler; Scott Kincaid; Trisha Branan; David Cluck; et al. (Antibiotics, 2020)
Objectives: There is debate on whether the use of third-generation cephalosporins (3GC) increases the risk of clinical failure in bloodstream infections (BSIs) caused by chromosomally-mediated AmpC-producing Enterobacterales (CAE). This study evaluates the impact of definitive 3GC therapy versus other antibiotics on clinical outcomes in BSIs due to Enterobacter, Serratia, or Citrobacter species. Methods: This multicenter, retrospective cohort study evaluated adult hospitalized patients with BSIs secondary to Enterobacter, Serratia, or Citrobacter species from 1 January 2006 to 1 September 2014. Definitive 3GC therapy was compared to definitive therapy with other non-3GC antibiotics. Multivariable Cox proportional hazards regression evaluated the impact of definitive 3GC on overall treatment failure (OTF) as a composite of in-hospital mortality, 30-day hospital readmission, or 90-day reinfection. Results: A total of 381 patients from 18 institutions in the southeastern United States were enrolled. Common sources of BSIs were the urinary tract and central venous catheters (78 (20.5%) patients each). Definitive 3GC therapy was utilized in 65 (17.1%) patients. OTF occurred in 22/65 patients (33.9%) in the definitive 3GC group vs. 94/316 (29.8%) in the non-3GC group (p = 0.51). Individual components of OTF were comparable between groups. Risk of OTF was comparable with definitive 3GC therapy vs. definitive non-3GC therapy (aHR 0.93, 95% CI 0.51–1.72) in multivariable Cox proportional hazards regression analysis. Conclusions: These outcomes suggest definitive 3GC therapy does not significantly alter the risk of poor clinical outcomes in the treatment of BSIs secondary to Enterobacter, Serratia, or Citrobacter species compared to other antimicrobial agents.